دور رأس المال المعرفي في تعزيز النجاح الاستراتيجي - مروان زبيدي; محمد الامين تجيني; ام الهناء مراد; اشراق منصوري (جامعة الوادي university of eloued, 2024)
هدفت هذه الدراسة الى معرفة دور رأس المال المعرفي في تعزيز النجاح الاستراتيجي دراسة حالة مخبر المجد للتحاليل الطبية بالوادي، ولتحقيق هدف الدراسة اعتمدنا على المنهج الوصفي التحليلي، وتمثلت متغيرات الدراسة في رأس المال المعرفي بأبعاده ) الخبرة ، المعرفة ، القدرة ، المهارة ( وتعزيز النجاح الاستراتيجي، تم استخدام الاستبيان كأداة لجمع البيانات، وبلغ عدد العينة 40 فرد من عمال المخبر وباستخدام برنامج SPSS V21 لتحليل البيانات توصلت الدراسة الى وجود دور لرأس المال المعرفي في تعزيز النجاح الاستراتيجي بمخبر المجد ،كما اوصت الدراسة بضرورة الاهتمام أكثر و استثمار في رأس المال المعرفي ومحاول إزالة الطبقات الإدارية مع العمال للفهم الجيد للعمال من الجانب المعرفي من طرف الإدارة. "This study aimed to understand the role of knowledge capital in enhancing strategic success, with a case study of Al-Majd Medical Analysis Laboratory in El Oued. To achieve the study’s objective, we relied on the descriptive analytical method. The study variables consisted of knowledge capital with its dimensions (expertise, knowledge, ability, skill) and strategic success. A questionnaire was used as a tool for data collection, and the sample size was 40 individuals from the laboratory’s staff. Using the SPSS V21 software for data analysis, the study concluded that knowledge capital plays a role in enhancing the strategic success of Al-Majd Laboratory. The study also recommended the need for greater attention to and development of knowledge capital and efforts to remove administrative layers between workers and management for better understanding of the workers’ knowledge aspects by the administration. "
Keywords: رأس المال المعرفي، المعرفة، الخبرة، القدرة، المهارة، تعزيز النجاح الاستراتيجي Knowledge capital; knowledge; experience; ability; skill; enhancing strategic success